Maturation signatures of conventional dendritic cell subtypes in COVID‐19 suggest direct viral sensing. Issue 1 (1st October 2021) - Marongiu, Laura; Protti, Giulia; Facchini, Fabio A.; Valache, Mihai; Mingozzi, Francesca; Ranzani, Valeria; Putignano, Anna Rita; Salviati, Lorenzo; Bevilacqua, Valeria; Curti, Serena; Crosti, Mariacristina; Sarnicola, Maria Lucia; et al.
Abstract: Growing evidence suggests that conventional dendritic cells (cDCs) undergo aberrant maturation in COVID‐19, which negatively affects T‐cell activation. The presence of effector T cells in patients with mild disease and dysfunctional T cells in severely ill patients suggests that adequate T‐cell responses limit disease severity. Understanding how cDCs cope with SARS‐CoV‐2 can help elucidate how protective immune responses are generated. Here, we report that cDC2 subtypes exhibit similar infection‐induced gene signatures, with the upregulation of IFN‐stimulated genes and IL‐6 signaling pathways. Furthermore, comparison of cDCs between patients with severe and mild disease showed severely ill patients to exhibit profound downregulation of genes encoding molecules involved in antigen presentation, such as MHCII, TAP, and costimulatory proteins, whereas we observed the opposite for proinflammatory molecules, such as complement and coagulation factors. Thus, as disease severity increases, cDC2s exhibit enhanced inflammatory properties and lose antigen presentation capacity. Moreover, DC3s showed upregulation of anti‐apoptotic genes and accumulated during infection. Direct exposure of cDC2s to the virus in vitro recapitulated the activation profile observed in vivo. Our findings suggest that SARS‐CoV‐2 interacts directly with cDC2s and implements an efficient immune escape mechanism that correlates with disease severity by downregulating crucial molecules required for T‐cell activation. Abstract : DC2s and DC3s show similar gene signatures in response to SARS‐CoV‐2 infections, and their activation responses are dominated by ISGs. cDC2 subtypes enhance their inflammatory properties and progressively lose antigen presenting functions as disease severity increases. DC2s and DC3s can be activated by direct viral sensing.